PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, KINERJA KEUANGAN, DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2020 - Diputra, Catherine Evelyn; Rasyid, Rosmita (Jurnal Paradigma Akuntansi, 2025)
This study was conducted with the aim of knowing the effect of firm size, capital structure, financial performance, and audit quality on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2020. A total of 100 sample data from manufacturing companies during the period of 2018-2020 using purposive sampling method have been collected using Microsoft Excel 2013. Furthermore, the data can be processed using EViews 12 software, in order to find out the results of hypothesis testing using multiple linear regression models. The result of the study indicate that firm size has negative effect on firm value, capital structure and financial performance have a positive effect on firm, while audit quality has no positive effect on firm value.